(untitled) (Proceedings of the International Conference on Public Health, 2019)
A Clinical Pathway is a comprehensive method of planning, delivering, and monitoring patient care. As efforts continue to streamline the delivery of services at all levels of care and settings, it is essential that quality management and utilization management professionals respond in a proactive manner to facilitate quality outcomes while decreasing cost and increasing efficiency. The aim of a Clinical Pathway is to enhance the quality of care across the continuum by improving risk-adjusted patient outcomes, promoting patient safety, increasing patient satisfaction, and optimizing the use of resources. However, there has not been any report on the implementation of the Clinical Pathway in Oral and Maxillofacial Surgery services in Indonesia. This research used observational methods and cross sectional design, with observational analysis and binary logistic regression. The population of this research was Clinical Pathway of Odontectomy were collected from medical records during January to December 2017 in ward surgery room of Dr. Soetomo hospital in Surabaya Indonesia. The Result obtained in this study, mostly completeness of Clinical Pathway were filled as the pattern. The amount of the sample in this research were 41 Clinical Pathway, which 87,8 % were fit according to the quality and cost indicator. The Variation in drug administration, treatment, and operator did not significantly influence (chi square = 0,93 ; df= 0 ; p value =1,00000 )